Expectation of Employers towards Quantity Surveying Students - Tan, Elaine Siew Ting (2015)
The role of a Quantity Surveyor in Malaysia has progressively changed according to the increase on the building project and complexity of the project. The roles of Quantity Surveying will also change according to the client request, the client not only expect the traditional services to be provided, but also additional services. The additional services include risk management, waste management, take turns as arbitrator; carry out feasibility study and so on. Fresh graduate arc no longer keep doing measurement, documentation, some estimating work, but further expand to another job scope. High employability skills and abilities can make a fresh graduate can stand at the competitive and global market in the construction industry. Hence the objective of this research is to define the competencies possess by Quantity Surveying student and to analyses what are the main expectation of Employers toward Quantity Surveying fresh graduate. The data will be analysis by using descriptive data analysis, frequency analysis and weighted average index. Overall, the research will provide the outcome on the expectation of Employer’s toward fresh graduate in term of hard skills, soft skills and computer literate for a better understanding for fresh graduate.